LINTASAN BELAJAR: ANALISIS DATA FASE A DALAM KONTEKS MAKANAN KHAS BERBAHAN DASAR SINGKONG DARI KARANGNONGKO DENGAN PENDEKATAN PMRI: Ethnomathematical Study of Snacks Made from Cassava Typical of Karangnongko in Data Analysis Mathematics - Furqon, Muhamad Nailul; Basar, Abdullah; Zuliana, Eka (Yayasan Al-Amin Qalbu, 2024)
This research aims to explore the learning trajectory of data analysis in the Fase A class using the case study or action research method in the context of traditional food from cassava with the PMRI (Indonesian Realistic Mathematics Education) approach. The focus of this research is on the diversity of traditional foods made from cassava. The research method used is action research which involves Fase A class students in understanding and analyzing data related to traditional food that uses cassava as the main ingredient. Through the PMRI approach, students are encouraged to understand not only the mathematical aspects of the data, but also the cultural aspects and local wisdom related to the food. The results of this research indicate that by applying PMRI in teaching, students can be more actively involved in collecting, analyzing and interpreting data about traditional cassava food. They learn how to convert quantitative information into a deeper qualitative understanding of the rich culture around them